2011
DOI: 10.1177/0954408911400008
|View full text |Cite
|
Sign up to set email alerts
|

Realizing sustainable process improvement through an understanding of machine–material interaction: part 1 – a methodology for audit, investigation, and improvement

Abstract: In striving to become world class, manufacturing organizations employ an array of tools and methods to support improvement programmes to increase quality, efficiency, flexibility, and ultimately reduce unit cost and increase capability. However, many of these programmes are destined to fail at the outset, either in part or in full, due to a lack of holistic and fundamental understanding of the production system, its constituent processes, raw materials, and the product. In addition to this deficiency in unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Details of these films are given in Table . As with any machine–material interaction scenario, it is important that all factors, which might serve in the sealability of the respective films, be measured and controlled. Previous studies have shown that the bending stiffness and the coefficient of friction (CoF; crimp material against film) have effects where forming and crimping take place.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Details of these films are given in Table . As with any machine–material interaction scenario, it is important that all factors, which might serve in the sealability of the respective films, be measured and controlled. Previous studies have shown that the bending stiffness and the coefficient of friction (CoF; crimp material against film) have effects where forming and crimping take place.…”
Section: Experimental Approachmentioning
confidence: 99%
“…The reasons for this have been previously reported (Hicks and Matthews [11]) and a lack of fundamental understanding of the system and what are referred to as MMIs identified as the underlying cause. To address this gap, a supportive methodology has been created and reported in detail (Hicks and Matthews [12]). The methodology provides a structured approach to the auditing, investigation, and improvement of MMIs and adopts a functional perspective enabling a formalization of interdisciplinary knowledge, including product, machine, process, and materials.…”
Section: Discussionmentioning
confidence: 99%
“…The four stages include the logical decomposition of the production process/ system into operations; the characterization of machine-material functions (MMFs); the decomposition of MMFs into individual MMIs; and the investigation (mapping) of each MMI through R-I diagrams [11]. The rationale of the eight steps is discussed in detail in [12] and the undertaking of the eight steps for the industrial case is now described.…”
Section: Auditmentioning
confidence: 99%
See 2 more Smart Citations